Current performance of Walton mobile in comparison with the competitors and effectiveness of its promotional activities - Hasan, Md. Mehedi (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.